ANALISIS ANGGARAN MATERIAL PROYEK SEBAGAI ALAT PENGENDALIAN BIAYA PADA PERUSAHAAN KONSTRUKSI - reny mony (Universitas Gajayana Malang, 2019)
The purpose of this research is to find out whether the material budget can be used as cost control tool or not on CV Niny Pratama in project work and to find out the form of control done to reduce deviation. The data were obtained directly from CV Niny Pratama Ambon and were analyzed using variance analysis method. The analysis carried out includes material quantity and material price analysis. The data obtained were in form of Budget Plan (RAB) and the realization of Leihitu District Pustu Improvement project becoming Non-Inpatient Health Center. The result of this research indicated that material cost budget plan has functioned well as cost control tool seen from no adverse variants yet the company succeeds to grow variant that is profitable from material quantity and price. It because material quantity and price are actually lower than what has been budgeted.